Implementation of Form-Focused Written Feedback on Students' Academic Writing - Wirantaka, Andi; Rosiah, Rosi; Baharun, Hazleena (Universitas Muhammadiyah Yogyakarta, 2026)
Academic writing skills are important, yet they present significant challenges due to their formal structure, linguistic accuracy, and the need for critical thinking. This research investigates the effectiveness of form-focused written feedback in improving students' academic writing skills. Using a quantitative experimental design, this study involved forty English department students at a university in Yogyakarta. Data were analyzed using a t-test after normality and homogeneity tests. The results revealed a statistically significant improvement in students' post-test scores relative to their pre-test scores on an academic writing test (p-value = 0.00 < 0.05), indicating the effectiveness of form-focused written feedback in enhancing academic writing skills. This study contributes new insights into the role of form-focused written feedback in academic writing at the university level, highlighting its value in fostering accuracy and students’ writing confidence.